Safety and efficacy of anti-programmed death 1 antibodies in patients with cancer and pre-existing autoimmune or inflammatory disease. (March 2018) - Danlos, François-Xavier; Voisin, Anne-Laure; Dyevre, Valérie; Michot, Jean-Marie; Routier, Emilie; Taillade, Laurent; Champiat, Stéphane; Aspeslagh, Sandrine; Haroche, Julien; Albiges, Laurence; Massard, Christophe; Girard, Nicolas; et al.
Abstract: Objective: Patients with autoimmune or inflammatory disease (AID) are susceptible to immune-related adverse events (irAEs) when treated with immune check-point inhibitors (ICIs). We decided to analyse the safety and effectiveness of anti-PD-1 antibodies in AID patients and look for an association between the presence of pre-existing AID and the clinical outcome. Methods: In a prospective study of the REISAMIC registry of grade ≥2 irAEs occurring in ICI-treated patients, we studied the associations between pre-existing AID on one hand and irAE-free survival, overall survival and best objective response rate on the other. Results: We identified 45 patients with 53 AIDs in REISAMIC. The cancer diagnoses included melanoma (n = 36), non–small-cell lung cancer (n = 6) and others (n = 3). The most frequent pre-existing AIDs were vitiligo (n = 17), psoriasis (n = 12), thyroiditis (n = 7), Sjögren syndrome (n = 4) and rheumatoid arthritis (n = 2). Twenty patients (44.4%) presented with at least one irAE: eleven of these were associated with a pre-existing AID ('AID flare'). Treatment with anti-PD-1 antibodies was maintained in 15 of the 20 patients with an irAE. The IrAE-free survival time was significantly shorter in AID patients (median: 5.4 months) than in AID-free patients (median: 13 months, p = 2.1 × 10 −4 ). The AID and AID-free groups did not differ significantly with regard to the overall survival time and objective response rate (p = 0.38 and 0.098, respectively). Conclusion: In patients treated with anti-PD-1 antibody, pre-existing AID was associated with a significantly increased risk of irAEs. Our results indicate that cancer treatments with anti-PD-1 antibodies are just as effective in AID patients as they are in AID-free patients. Highlights: In patients treated with anti-PD-1 antibodies, the presence of a pre-existing auto-immune or inflammatory disease is associated with a higher risk of immune-related adverse events. Immunotherapies provide similar levels of effectiveness (overall survival) in patients with and without pre-existing auto-immune or inflammatory disease. Half of these immune-related adverse events are flares or manifestations of the pre-existing autoimmune or inflammatory disease. Anti-PD-1 antibodies can be maintained in 75% of the patients despite the immune-related adverse events.